Penyuluhan Edukasi Bahaya Merokok Di SMP Negeri 11 Sigi - Wulandari, Sinta; Jamila, Sofia; Rabiah, Rabiah; Mardini, Rusna S; Magelo, Widya Grasela; Pratiwi, Ananda (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Tobacco use is a global problem that causes death in the world. Tobacco smoking is a risk factor for six out of eight causes of premature death, namely ischemic heart disease, cerebrovascular disease, lower respiratory tract infections, chronic obstructive pulmonary disease, tuberculosis and cancer of the trachea, bronchi and lungs. Individuals who develop smoking behaviors in their early teens also have an increased risk of cardiovascular disease, respiratory disease, and cancer, and they are more likely to experiment with alcohol and other drugs. The Education Counseling on the Dangers of Smoking includes an explanation of the Dangers of Smoking and the effects that smokers can have. The education also provides knowledge on how to prevent smokers. With the existence of health education given to adolescents, it will add to the knowledge of adolescents about the dangers of smoking.